Greenhouse Gas Emissions from an Apartment-Scale Aerobic Sewage Treatment Plant - Andry Daniel Dethan; Awaluddin Hidayat Ramli Inaku (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study quantified greenhouse gas (GHG) emissions from an apartment-scale aerobic Sewage Treatment Plant (STP) in Surabaya using the 2019 IPCC Guidelines combined with a Scope 1–Scope 2 accounting framework. Direct emissions (Scope 1) consisted of methane (CH4) and nitrous oxide (N2O) generated from biological treatment processes, while indirect emissions (Scope 2) were associated with operational electricity consumption. Activity data from 2023–2025 included occupancy levels, wastewater flow rates, effluent quality, and equipment operation. Results showed that Scope 1 emissions increased from 6,689 to 8,256 kg CO2-eq/year due to rising occupancy, whereas Scope 2 emissions from electricity remained stable at 65,821 kg CO2/year. Total emissions ranged from 72,510 to 74,077 kg CO2-eq/year, with electricity contributing approximately 90% of the overall GHG profile. Per-capita emission intensity decreased from 161.5 to 133.7 kg CO2-eq/person/year as occupancy increased, while energy demand remained constant. These findings demonstrate that electricity use—particularly aeration energy—dominates the carbon footprint of apartment-scale aerobic STPs. The study highlights the importance of facility-level GHG inventories and indicates that energy efficiency improvement represents the most effective mitigation strategy for residential wastewater treatment systems. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and Sanitation SDG 11: Sustainable Cities and Communities SDG 13: Climate Action